The Representation of Ecocentric Discourse in Indonesian Language Textbooks for Junior High School - Farhan Aziz; Wiyatmi Wiyatmi; Esti Swatika Sari; Akbar Maulana (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
In the context of an escalating global environmental crisis, this study aims to address the crucial role of language teaching by comparatively analyzing the representation of ecocentric discourse in six official Indonesian junior high school language textbooks under the 2013 and Merdeka Curricula. Employing a qualitative content analysis methodology, the findings reveal a critical deficit of ecocentric content, with only 70 instances identified across all books. A systematic regression was observed, with ecocentric representations decreasing by grade level in both the 2013 Curriculum (from 41 to 9, then 3) and the Merdeka Curriculum (from 14 to 2, then 1). Comparatively, the newer Merdeka Curriculum, with only 17 total findings, exhibits a significant decline from the 2013 Curriculum's 53 findings. The study concludes that this marginalization of environmental discourse is not a reflection of authorial shortcomings but a systemic consequence of a centralized national textbook policy that reduces authorial autonomy. This research contributes a crucial empirical basis for advocating educational policy reform, urging the development of materials that systematically cultivate the ecological literacy required for a sustainable society.